PREPARED TO INCLUDE? PRE-SERVICE TEACHERS' PERCEPTIONS OF AI'S ROLE IN SUPPORTING DIVERSE LEARNERS WITHIN PUNJAB'S INITIAL TEACHER EDUCATION PROGRAMMES (Qualitative Research Journal for Social Studies, 2026)
Within Initial Teacher Education (ITE) in the province of Punjab, Pakistan, a gap separates national policy commitments to inclusion and the adoption of artificial intelligence (AI) in the classroom, and the lack of attention to these issues in pre-service teacher preparation. This study explored pre-service teachers' perceptions of how AI can be integrated to support inclusion in ITE in Punjab, Pakistan. Through Reflexive Thematic Analysis, we interviewed twenty pre-service teachers from four ITE departments in Punjab using semi-structured interviews. NVivo 15 software was used for data management. Four themes were identified: AI as an Imagined Equaliser, Competence Gap, Institutional Silence and Its Impact and Ethical Uncertainty at the Margins. Results suggest pre-service teachers have a hopeful but unstructured perception of the potential of AI for inclusion. The study provides local data to global discussions on AI literacy in teacher education, and highlights an urgency for inclusive AI pedagogies in ITE in Pakistan.